Radionuclide emissions from a coal-fired power plant - Amin, Yusoff Mohd; Khandaker, Mayeen Uddin; Shyen, A.K.S.; Mahat, R.H.; Nor, Roslan Md; Bradley, D.A. (Elsevier, 2013)
Current study concerns measurement of radioactivity levels in areas surrounding a 2420 MW thermal power plant fueled predominantly by bituminous coal. The concentrations of 226Ra, 232Th and 40K in onsite bottom-ash were found to be 139 Bq/kg, 108 Bq/kg and 291 Bq/kg, respectively, the levels for these radiolnuclides in soil decreasing with distance from the power plant. At the plant perimeter the respective radionuclide concentrations were 87 Bq/kg, 74 Bq/kg and 297 Bq/kg. In a nearby town, the corresponding concentrations were 104 Bq/kg, 52 Bq/kg and 358 Bq/kg, suggestive of use of TENORM affected soils. The mean radium equivalent activities (Raeq) in soil and ash sample in the town were 205 Bq/kg and 316 Bq/kg, respectively. The Kapar plant ash/slag appears to contain a higher level of TENORM than the world average. The degree of contamination is much higher inside the town where slag has been mixed with topsoil as landfill or as simple domestic waste. For the prevailing levels of exposure and a worst case senario, the predicted committed effective dose due to ingestion and inhalation for intake durations of 1- and 30 years would be 4.2 μSv and 220 μSv, respectively.